Securing old age vs. other saving goals of households - Sylwester Białowąs; Iwona Olejnik (Economic and Environmental Studies (E&ES), 2018)
The article presents households' motivations for saving, including - in particular - saving for retirement. It defines the notion of goals with reference to a more frequently described notion of motives. On the basis of the authors' own empirical research results, the relationship between saving for retirement and other goals of saving was found, as well as verifying and comparing the determinants of particular goals of saving. The analysis uses the methods of descriptive statistics and logistic regression.
Keywords: D12; D14; 330; saving behaviour; motives for savings; goals of savings